Evaluasi Bank Syariah Indonesia Pasca Serangan Siber: Pergerakan Saham dan Kinerja - Solikhawati, Anisa; Samsuri, Andriani (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the movement of BRIS shares after the cyber attack on May 8 2023. BRIS, which is owned by PT. Bank Syariah Indonesia Tbk experienced a decrease in share price due to a system error. Digital transaction services had stopped, such as BSI Mobile, ATMs and tellers at branch offices unable to serve customers. This study uses a quantitative method with a descriptive approach. The results show that the stock price movement has decreased until June 26 2023 and BSI's performance seen from the KPMM, ROA and BOPO ratios received the criteria of being healthy and good. Meanwhile, the FDR ratio of Islamic banks is considered bad because it has poor liquidity.